A CONTROLLER'S CONCEPTION OF A MODERN ANNUAL REPORT. - Grace, John C. (The Accounting Review, 1949)
Abstract A recent survey by the Controllership Foundation to ascertain the public's acceptance of the facts and figures of business accounting disclosed several facts. The accountant is also confronted with the possibility that over-simplification of financial statements might easily result in confusion rather than clarity. The top managements, the controllers, the public accountants, the educators, the American Institute of Accountants, and the Controller's Institute of America have tremendous responsibility and an opportunity during the next five years to make the corporate annual report the keystone or media of communication to correct public and employee concepts of American business. Hence, improvements in financial statements and annual reports may well be the result of trial and error and certainly requires the exercise of good judgment and knowledge if continued improvement is to be had; innovations for innovation's sake are not satisfactory. Therefore, the controller and the public accountant are presented with a continuous challenge and grave responsibility to make the annual report more valuable and informative by their influence on its content and preparation; only through these combined efforts will the annual report gain the confidence of the public, labor unions, the investors and top management.